MANAJEMEN RADIO SWASTA JODHIPATI FM DALAM PELESTARIAN BUDAYA JAWA DI NGANJUK (Universitas Negeri Surabaya, 2021)
This study aims to determine the management of Jodhipati FM radio in the preservation of Javanese culture. This research method uses a case study with a qualitative approach. The research data were obtained from interviews, observations, and documentation of the focus of research on the management of Radio PT Jodhipati Nganjuk City in carrying out the principles of public broadcasting. The results of this study indicate that there is a collection of programs owned by Radio Suara Jodhipathi, Nganjuk City which has fulfilled the principles of public broadcasting such as programs that focus on identity, national culture and are available in general geographically and in accordance with the POAC management concept. The peculiarity of broadcasting institutions, this indicator shows that Radio Jodhipati is the only broadcasting institution that uses the regional language (Javanese) in Nganjuk seen from the segmentation and composition of broadcasts. Finance, Radio Jodhipati does not yet have an optimal financial management system, it still relies on existing capital so that it cannot produce events on a large scale.